Evaluation of NaTto Red Yeast Rice on Regulating Blood Lipid (ENTRY) Study: A Multicenter, Double‐Placebo, Double‐Blinded, Randomized Controlled Trial in Chinese Adults - Shufeng Chen; Fangchao Liu; Jinyue Li; Fengchao Liang; Jianxin Li; Jie Cao; Donghua Liu; Keyong Huang; Hongfan Li; Xiangfeng Lu; Jianfeng Huang; Dongfeng Gu (Chronic Diseases and Translational Medicine)
ABSTRACT Background Statins are the first line of treatment for dyslipidemia, but their side effects often reduce medication compliance. Natto and red yeast rice are natural ingredients with lipid‐lowering effects. However, the efficacy of Natto Red Yeast Rice (NRYR) supplement in combination with statins in regulating blood lipid levels has not been fully evaluated. Methods A multicenter, double‐blinded, randomized‐controlled trial was conducted among individuals with low‐density lipoprotein cholesterol (LDL‐C) of 3.4 to 5.0 mmol/L at six sites in China, of those at moderate risk of cardiovascular disease (CVD) are prioritized. Participants are enrolled and randomly assigned into four groups by a combination of NRYR (or its placebo) and Simvastatin (or its placebo) in a ratio of 1:1:1:1. After examination at baseline, all participants underwent intervention for 3 months and two follow‐up visits at 1 month and 3 months after the intervention. The primary outcome is the change in LDL‐C level at 3 months, and secondary outcomes include changes in levels of other lipid profiles and biomarkers, as well as calculated 10‐year CVD risk. A total of 1136 participants were randomly assigned, of whom 1110 received the intervention. Discussion This study may provide new evidence for the efficacy of NRYR supplement in combination with statins to regulate lipid levels and optimize lipid management. Trial Registration Chinese Clinical Trial Registry database: registration nos. ChiCTR2200064214, ChiCTR2200064215.